Clinical outcomes, hemodynamics, and leaflet thrombosis following transcatheter aortic valve replacement with novel intra‐annular devices - Juri Iwata; Kentaro Hayashida; Akiyoshi Kajino; Shingo Sakata; Shohei Imaeda; Toshinobu Ryuzaki; Hikaru Tsuruta; Hideyuki Shimizu; Masaki Ieda (Health Science Reports)
Abstract Background The indication of transcatheter aortic valve replacement (TAVR) is becoming more prevalent among younger and lower‐risk patients. However, data on the latest intra‐annular TAVR devices are limited. This study aims to compare the short‐term clinical outcomes of two intra‐annular transcatheter aortic valve replacement (TAVR) devices in Japan: SAPIEN 3 Ultra RESILIA (S3UR) and Navitor. Methods Of the 286 patients who underwent TAVR between May 2022 and October 2023 at our center, we enrolled 97 consecutive patients who received either S3UR or Navitor. We compared the intraprocedural invasive and echocardiographic hemodynamic assessment and post‐procedural multidetector computed tomography (MDCT). Results The basic characteristics of the 97 patients (median age, 86 years [interquartile range, 81–89 years]) were similar. Technical success, defined by the Valve Academic Research Consortium, was achieved in all cases. Despite a smaller annulus, Navitor demonstrated decreased mean pressure gradient by TTE, 9.2 [7.3–13.6] mmHg versus 7.5 [5.9–9.5] mmHg, p = 0.006; but not by invasive measurement 5.1 [3.4–7.7] mmHg versus 5.3 [3.2–7.9] mmHg, p = 0.986). Discordance between echocardiographic and invasive assessment was more prominent with S3UR. However, severe prosthesis‐patient mismatch was similarly noted between the two devices. Mild paravalvular leak (PVL) (24.5% vs. 54.5%, p = 0.002) was more frequent with the Navitor, despite no moderate‐severe PVL in each group. The incidence of hypoattenuated leaflet thickening (HALT) detected by MDCT was similar between the two groups. Conclusions Both intra‐annular valves demonstrated excellent hemodynamic performance with minimal PVL after TAVR. The incidence of HALT in both devices was comparable.